2018
DOI: 10.3390/ijerph15030485
|View full text |Cite
|
Sign up to set email alerts
|

Accidents of Electrical and Mechanical Works for Public Sector Projects in Hong Kong

Abstract: A study on electrical and mechanical (E&M) works-related accidents for public sector projects provided the opportunity to gain a better understanding of the causes of accidents by analyzing the circumstances of all E&M works accidents. The research aims to examine accidents of E&M works which happened in public sector projects. A total of 421 E&M works-related accidents in the “Public Works Programme Construction Site Safety and Environmental Statistics” (PCSES) system were extracted for analysis. Two-step clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
1
9
0
1
Order By: Relevance
“…This factor ranked sixth for minimising waste in time and fourth for minimising cost overrun. This result agrees with the findings of previous studies [12,72,73]. The importance of this factor lies in its containment: (1) preventing mistakes in supplies, (2) avoiding transport error and reducing supplier errors, (3) preventing mistakes in quantity surveys, (4) avoiding incorrect procedures of material delivery, (5) avoiding increase over the allocated quantities to purchase, (6) reducing the repetition of change orders and (7) reducing the waiting time for equipment replacement.…”
Section: Main Factors Of Ss With Positive Effects On Minimising Cw Dusupporting
confidence: 94%
“…This factor ranked sixth for minimising waste in time and fourth for minimising cost overrun. This result agrees with the findings of previous studies [12,72,73]. The importance of this factor lies in its containment: (1) preventing mistakes in supplies, (2) avoiding transport error and reducing supplier errors, (3) preventing mistakes in quantity surveys, (4) avoiding incorrect procedures of material delivery, (5) avoiding increase over the allocated quantities to purchase, (6) reducing the repetition of change orders and (7) reducing the waiting time for equipment replacement.…”
Section: Main Factors Of Ss With Positive Effects On Minimising Cw Dusupporting
confidence: 94%
“…The tools that were used, and the results obtained using them, are a good starting point for the analysis of accidents in the construction industry around the world. A similar study can be found in [19], in which an analysis of accidents related to electrical and mechanical work was carried out. In these studies, a two-stage cluster analysis was used.…”
Section: Literature Review-application Of Data Classification Methodsmentioning
confidence: 97%
“…Instalasi listrik di semua laboratorium telah terpasang dengan baik, ini perlu diperhatikan karena pekerjaan kelistrikan dapat mengakibatkan kecelakaan serius dan komplikasi dengan risiko tinggi (Wong et al, 2018;Gille et al, 2018). Catu daya juga harus dijauhkan dari area basah dan instalasi harus mematuhi peraturan keselamatan listrik setempat (WHO, 2020).…”
Section: Peralatan Listrikunclassified